Pemenuhan Hak Atas Informasi Masyarakat Dalam Pelaksanaan Pengadaan Tanah: Studi Pengadaan Tanah Taman Budaya Sleman - Siti Rahma Novikasari; Nurmalita Ayuningtyas Harahap (Jurnal Hukum IUS QUIA IUSTUM, 2021)
This research is aimed at examining the relationship between the implementation of the principle of openness of the government to the fulfillment of the right to information in the land acquisition activity of the Sleman Cultural Park. The problems in this research are, first, what is the concept of fulfilling the right to information in the land acquisition policy for the public interest? Second, does the implementation of the Sleman Cultural Park land acquisition reflect the fulfillment of the right to information? This study uses an empirical legal research method with a statutory approach and a conceptual approach. The results of the study concluded that in the implementation of the Sleman Cultural Park land acquisition, the fulfillment of the right to information by the government was limited to a formalistic framework and had not yet reached the fulfillment of the right to information substantially, so that the community did not have full rights to information. This has led to public distrust of the government and resulted in the failure of land acquisition activities for the Sleman Cultural Park.